Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1159/000232577
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Insulin Resistance after Kidney Donation: A Pilot Observational Study

Abstract: Background: In chronic kidney disease the contribution of decreased glomerular filtration rate (GFR) versus enhanced inflammation to cause insulin resistance (IR) is controversial. Aim: This pilot observational study examines, therefore, the prevalence of IR after kidney donation and factors that may determine its level. Methods: Insulin, proinsulin, adiponectin, malondialdehyde, and hsCRP were measured by conventional techniques in 14 previous kidney donors and 25 healthy volunteers. Results: Estimated GFR fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…These findings support the notion that adipose cells, not accumulating leukocytes, are essential contributors to the PAT-specific activation of RAS and that PAT-specific activation of RAS con- Plasma insulin levels after glucose loading are markedly elevated in uninephrectomized apoE Ϫ/Ϫ mice. Of the various substances upregulating angiotensinogen gene expression in adipose cells (21)(22)(23)(24)(25)(26), we focused on insulin signaling because renal insufficiency has been reported to increase plasma insulin levels to compensate for insulin resistance in both animal experiments and clinical studies (3,19,35). While the plasma insulin levels under fasting conditions did not differ between the two groups, the homeostasis model assessment-insulin resistance (HOMA-IR) index for 16-wk-old UNX mice was significantly higher than for sham control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the notion that adipose cells, not accumulating leukocytes, are essential contributors to the PAT-specific activation of RAS and that PAT-specific activation of RAS con- Plasma insulin levels after glucose loading are markedly elevated in uninephrectomized apoE Ϫ/Ϫ mice. Of the various substances upregulating angiotensinogen gene expression in adipose cells (21)(22)(23)(24)(25)(26), we focused on insulin signaling because renal insufficiency has been reported to increase plasma insulin levels to compensate for insulin resistance in both animal experiments and clinical studies (3,19,35). While the plasma insulin levels under fasting conditions did not differ between the two groups, the homeostasis model assessment-insulin resistance (HOMA-IR) index for 16-wk-old UNX mice was significantly higher than for sham control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the serum concentration of fatty acids at 16 wk of age; however, UNX mice showed the similar concentration levels of fatty acid as those observed in control mice. Clinical studies have demonstrated that CKD patients are susceptible to insulin resistance accompanied by postprandial hyperglycemia (3,19,35), and insulin stimulation has been shown to regulate AGT gene expression in adipose cells (2,15). We thus examined the plasma insulin level and insulin resistance in UNX mice and found that UNX mice exhibited insulin resistance with a significantly higher plasma insulin level after glucose loading (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nephrectomy-associated increase of RBP4 serum concentrations may explain the increased susceptibility of living-kidney donors for insulin resistance as "described by Shehab-Eldin et al [35]. However, since the present study was an observational study, which primary aim was to analyze the nephrectomy-associated changes in ROH, RBP4 and TTR in living-kidney donors, the association of the vitamin A transport complex with CVD and insulin resistance remains speculative and should be a matter of future research.…”
Section: Discussionmentioning
confidence: 99%
“…This is the leading cause of death in kidney transplant recipients [56]. Transplant is also associated with insulin resistance and inflammation [63]. Furthermore, immunosuppressive agents per se can induce insulin resistance and diabetes [64].…”
Section: Ezetimibe As a Potential Treatment For Dyslipidaemia Associamentioning
confidence: 99%